Geochemistry of Lower Cretaceous sediments, Inner Zone of Southwest Japan: Constraints on provenance and tectonic environment - Asiedu, D.K.; Suzuki, S.; Nogami, K.; Shibata, T. (Geochemical Journal, 2000)
A geochemical study was carried out on Lower Cretaceous sedimentary rocks of the Wakino Subgroup, Kenseki Formation, and Sasayama Group, distributed in the Inner Zone of Southwest Japan. The chemical characteristics of the Lower Cretaceous sediments indicate that these rocks are immature first-order sediments derived from igneous and/or meta-igneous rocks of predominantly felsic composition. The sediments from the Kenseki Formation and the Sasayama Group, however, show high Cr and Ni abundances, suggesting a significant contribution of detritus from ultramafic rocks. Weathering at the source areas was moderate. The high Th/U ratios (mostly >3.8), negative Eu anomalies (Eu/Eu(*) between 0.67 and 0.93) and Th/Sc ratios (mostly between 0.5 and 1) of the Lower Cretaceous sediments suggest their derivation dominantly from an old upper crust with minor amounts of young arc-derived detritus. The major, trace and rare earth element compositions imply that deposition took place in an active continental margin environment. The small amounts of young arc-derived material in the sediments support the inference by other workers that arc magmatism was not so prominent in Southwest Japan during the early Cretaceous.
Keywords: Geochemistry; Lower Cretaceous sediments; Japan; Tectonic environment